2019
DOI: 10.1021/jacs.9b02693
|View full text |Cite
|
Sign up to set email alerts
|

A Self-Assembled Organic/Metal Junction for Water Photo-Oxidation

Abstract: We report the in situ self-assembly of TTF, TTF•+, and BF4 – or PF6 – into p-type semiconductors on the surface of Pt microparticles dispersed in water/acetonitrile mixtures. The visible light photoactivation of these self-assemblies leads to water oxidation forming O2 and H+, with an efficiency of 100% with respect to the initial concentration of TTF•+. TTF•+ is then completely reduced to TTF upon photoreduction with water. The Pt microparticles act as floating microelectrodes whose Fermi level is imposed by … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
25
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 15 publications
(27 citation statements)
references
References 86 publications
2
25
0
Order By: Relevance
“…We have previously reported the in situ stabilization of metal nanoparticles such as Co in a TAPA‐containing porous matrix for enhanced electrocatalytic activity . With the aim of increasing the H 2 evolution, we envisioned that the in situ stabilization of Pt nanoparticles on the CMP matrices could be advantageous, as the photogenerated electron can easily reach the surface‐attached Pt nanoparticles without recombination . Thus, we stabilized Pt nanoparticles in situ in the CMP matrices (see Experimental Section), which was confirmed by TEM analysis, EDAX, and elemental mapping (Figure , and Figures S18–S20, Supporting Information).…”
Section: Resultssupporting
confidence: 58%
See 1 more Smart Citation
“…We have previously reported the in situ stabilization of metal nanoparticles such as Co in a TAPA‐containing porous matrix for enhanced electrocatalytic activity . With the aim of increasing the H 2 evolution, we envisioned that the in situ stabilization of Pt nanoparticles on the CMP matrices could be advantageous, as the photogenerated electron can easily reach the surface‐attached Pt nanoparticles without recombination . Thus, we stabilized Pt nanoparticles in situ in the CMP matrices (see Experimental Section), which was confirmed by TEM analysis, EDAX, and elemental mapping (Figure , and Figures S18–S20, Supporting Information).…”
Section: Resultssupporting
confidence: 58%
“…[22] With the aim of increasing the H 2 evolution, we envisioned that the in situ stabilization of Pt nanoparticles on the CMP matrices could be advantageous, as the photogenerated electron can easily reach the surface-attached Pt nanoparticles withoutr ecombination. [68] Thus, we stabilized Pt nanoparticles in situ in the CMP matrices( see Experimental Section), which was confirmed by TEM analysis, EDAX, and elemental mapping (Figure 3, and Figures S18-S20, Supporting Information). The quantification of Pt nanoparticles in the CMP matrix was achieved through elemental mapping, EDAX, and ICP analysis,w hich support the presenceo fa round6a nd 8wt% Pt nanoparticles in the TAPA-OPE-mix and TAPA-OPE-gly,r espectively ( Figure S20).…”
Section: Resultsmentioning
confidence: 99%
“…In a recent publication, we have shown that we could use the concept of redox electrocatalysis for photo-oxidising water, using tetrathiafulvalene cations TTF + , as a sensitiser and TTF as the redox mediator 23) . In this work, the water oxidation takes place in a water-acetonitrile mixture to dissolve the organic salts and to provide excess water for the reactions.…”
Section: Molecular Electrocatalysts For Water Splittingmentioning
confidence: 99%
“…Their works have also established the role of the distant functional groups on the porphyrin ring towards stabilizing the concerned catalysts under the high oxidizing environment of OER. Several research groups reported efficient OER by molecular metal porphyrins per se , and also by metal porphyrins, impregnated on heterogeneous supports [19,37–39] . In the last few years, a notable amount of research has been carried out in the field of porphyrin and metal porphyrin containing MOFs [5,36,39–41] .…”
Section: Introductionmentioning
confidence: 99%
“…Several research groups reported efficient OER by molecular metal porphyrins per se , and also by metal porphyrins, impregnated on heterogeneous supports [19,37–39] . In the last few years, a notable amount of research has been carried out in the field of porphyrin and metal porphyrin containing MOFs [5,36,39–41] . The porphyrin molecules are either used as metalloligands or as guest/post‐synthetically incorporated species sitting in the void inside the MOF.…”
Section: Introductionmentioning
confidence: 99%